From Manifesto to Social Practice: Internalising the Values of Risalah Islam Berkemajuan in Muhammadiyah Vocational Education - Darul Qutni Hakiki; Ilham Kamaruddin; Hamdan Saleh; Heri Rifhan Halili (PT. Education Research Center, 2026)
Social change, digital transformation, and evolving labour market demands require Islamic education to cultivate religious, adaptive, critical, and socially engaged students. This study explores how the values of Risalah Islam Berkemajuan are internalised in vocational education at SMK Muhammadiyah Tanjung Selor. Using a qualitative case study design, data were collected through semi-structured interviews and document analysis. Hybrid thematic analysis combined inductive interpretation of participants’ experiences with deductive analysis based on the framework of Risalah Islam Berkemajuan. The findings reveal five patterns: adaptive religious learning rooted in the Qur’an and Sunnah; tauhid as the foundation of character formation; learning innovation, critical thinking, and a culture of knowledge; integration of religion and knowledge through social and environmental responsibility; and student participation in socio-religious life. These values are internalised through faith, pedagogical innovation, knowledge development, and social practice.